Co-Chaperone Bag-1 Plays a Role in the Autophagy-Dependent Cell Survival Through Beclin 1 Interaction - Türk, Miray; Tatlı, Özge; Alkan, Hamza Furkan; KILBAŞ, PELİN ÖZFİLİZ; Alkurt, Gizem; Dinler Doğanay, Gizem (MDPI, 2021)
Expression levels of the major mammalian autophagy regulator Beclin 1 and its interaction with Bcl-2 regulate the switch between autophagic cell survival and apoptotic cell death pathways. However, some of the regulators and the precise mechanisms of these processes still remain elusive. Bag-1 (Bcl-2 associated athanogene-1), a member of BAG family proteins, is a multifunctional pro-survival molecule that possesses critical functions in vital cellular pathways. Herein, we report the role of Bag-1 on Bcl-2/Beclin 1 crosstalk through indirectly interacting with Beclin 1. Pull-down experiments suggested a molecular interaction between Bag-1 and Beclin 1 in breast cancer cell lines. On the other hand, in vitro binding assays showed that Bag-1/Beclin 1 interaction does not occur directly but occurs through a mediator molecule. Bag-1 interaction with p-Beclin 1 (T119), indicator of early autophagy, is increased during nutrient starvation suggesting involvement of Bag-1 in the autophagic regulation. Furthermore, CRISPR/Cas9-mediated Bag-1 knock-out in MCF-7 cells hampered cell survival and proliferation and resulted in decreased levels of total LC3 under starvation. Collectively, we suggest that Bag-1 modulates cell survival/death decision through maintaining macroautophagy as a component of Beclin 1-associated complexes.
Keywords: Bag-1; Bcl-2; Beclin 1; Autophagy; Breast Cancer